Use of different adsorbents in broiler diets naturally contaminated by mycotoxins - Groff-Urayama, Priscila Michelin [UNESP] (2022)
This study investigated the effects of adding different adsorbent substances to broilers feed naturally contaminated by mycotoxins. Two hundred and eighty male 1-day-old chicks, Cobb Slow® lineage, were distributed in a randomized block design with 4 treatments, 5 repetitions with 14 birds each. The treatments consisted of: T1- basal feed naturally contaminated with mycotoxins. T2- basal feed + Bentonite, Thistle Extract, Yeast Extract, Vitamin E and Choline. T3- basal feed + Bentonite, Thistle Extract, yeast cell wall and Silymarin. T4- basal feed + Bentonite and Algae extract. Performance (weight gain, feed intake, feed conversion) at 7, 14, 21, 28 days were evaluated. At 28 days, a portion of the jejunum was collected in two birds by replicate to study the intestinal morphology. The relative weight of the gizzard, proventricle and total intestine was evaluated. The data obtained were analyzed using the statistical program SAS (9.3). With the use of any adsorbents studied, the performance and liver weight were improved in all evaluated periods. Thus, the inclusion of adsorbents improves the performance of the broiler chickens when the feed is contaminated by mycotoxins.